Nursing Care for Mrs. S With Sensory Perception Disorder: Auditory Hallucinations Due to Schizophrenia Nur Illahi Assani Clinic, Samarang - Daniati, Eva; Permana, Gin Gin Sugih (CV. Literasi Publikasi Indonesia, 2024)
This case study on patients with auditory hallucinations was taken as this scientific research, because hallucinations are a symptom that is often found in people with mental disorders, especially schizophrenia. The purpose of making this scientific paper is to gain knowledge, skills, insights and real experience in providing comprehensive nursing care. The method used by the author is a descriptive method through case studies with data collection and observation techniques. The subject of the study is schizophrenia with auditory hallucination nursing problems which are carried out starting from the assessment, diagnosis, intervention, implementation, and evaluation stages. Hallucinations are a condition that describes the presence of a wrong sensory perception, which may affect one of the five senses. Nursing care was carried out for 5 days (April 26 - May 1). The author found two problems experienced by the patient, namely sensory perception disorder: auditory hallucinations and self-concept disorder: low self-esteem. However, the focus or main goal of providing this nursing care is to improve the patient's perception, and the patient can relate to reality. The author also carried out nursing actions using the principles of therapeutic communication, motivating the patient to control her hallucinations. The author evaluated the nursing implementation so that we obtained data that the patient was able to control her hallucinations even with the support of the nurse.